Respiratory‐gated KES imaging of a rat model of acute lung injury at the Canadian Light Source. (24th March 2017) - Deman, P.; Tan, S.; Belev, G.; Samadi, N.; Martinson, M.; Chapman, D.; Ford, N. L.
Abstract : A K ‐edge subtraction imaging approach for respiratory‐gated lung imaging using iodine and xenon contrast agents in a rodent model is presented. Abstract : In this study, contrast‐enhanced X‐ray tomographic imaging for monitoring and quantifying respiratory disease in preclinical rodent models is proposed. A K ‐edge imaging method has been developed at the Canadian Light Source to very accurately obtain measurements of the concentration of iodinated contrast agent in the pulmonary vasculature and inhaled xenon in the airspaces of rats. To compare the iodine and xenon concentration maps, a scout projection image was acquired to define the region of interest within the thorax for imaging and to ensure the same locations were imaged in each K ‐edge subtraction (KES) acquisition. A method for triggering image acquisition based on the real‐time measurements of respiration was also developed to obtain images during end expiration when the lungs are stationary, in contrast to other previously published studies that alter the respiration to accommodate the image acquisition. In this study, images were obtained in mechanically ventilated animals using physiological parameters at the iodine K ‐edge in vivo and at the xenon K ‐edge post mortem (but still under mechanical ventilation). The imaging techniques were performed in healthy Brown Norway rats and in age‐matched littermates that had an induced lung injury to demonstrate feasibility of the imaging procedures and the ability to correlate the lung injury and the quantitative measurements of contrast agent concentrations between the two KES images. The respiratory‐gated KES imaging protocol can be easily adapted to image during any respiratory phase and is feasible for imaging disease models with compromised lung function.